Integrative systems medicine approaches to identify molecular targets in lymphoid malignancies. Issue 1 (December 2016) - Frazzi, Raffaele; Auffray, Charles; Ferrari, Angela; Filippini, Perla; Rutella, Sergio; Cesario, Alfredo
Abstract Although survival rates for lymphoproliferative disorders are steadily increasing both in the US and in Europe, there is need for optimizing front-line therapies and developing more effective salvage strategies. Recent advances in molecular genetics have highlighted the biological diversity of lymphoproliferative disorders. In particular, integrative approaches including whole genome sequencing, whole exome sequencing, and transcriptome or RNA sequencing have been instrumental to the identification of molecular targets for treatment. Herein, we will discuss how genomic, epigenomic and proteomic approaches in lymphoproliferative disorders have supported the discovery of molecular lesions and their therapeutic targeting in the clinic.